Non-price competitiveness of exports from emerging countries - Konstantins Benkovskis; Julia Wörz (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
This analysis of global competitiveness of emerging market economies accounts for non-price aspects of competitiveness. Building on the methodology pioneered by Feenstra (1994) and Broda and Weinstein (2006), we construct an export price index that adjusts for changes in the set of competitors (variety) and changes in non-price factors (quality in a broad sense) for nine emerging economies (Argentina, Brazil, Chile, China, India, Indonesia, Mexico, Russia and Turkey). The highly disaggregated dataset covers the period 1999?2010 and is based on the standardized 6-digit Harmonized System (HS). Unlike studies that use a CPI-based real effective exchange rate, our method highlights notable differences in non-price competitiveness across markets. China shows a huge gain in international competitiveness due to non-price factors, suggesting that China critics may be overstressing the role of renminbi undervaluation in explaining China's competitive position. Oil exports account for strong improvement in Russia's non-price competitiveness, as well as the modest losses of competitiveness for Argentina and Indonesia. Brazil, Chile, India and Turkey show discernible improvements in their competitive position when accounting for non-price factors. Mexico's competitiveness deteriorates regardless of the index chosen.
URN:NBN:fi:bof-201408072134
Keywords: C43; F12; F14; L15; 330; non-price competitiveness; quality; relative export price; emerging countries